Assessing five years of the African Continental Free Trade Area (AfCFTA): Proposals on potential amendments - Kiiza Africa (South Centre, 2025)
On 30th May 2024, the African Continental Free Trade Area (AfCFTA) celebrated its fifth anniversary, which legally implied that the agreement is up for review for possible amendments. To kickstart this review, the Thirty-Seventh Ordinary Session of the African Union Summit (held in February 2024) directed the AfCFTA Secretariat to take necessary measures for the start of the review of the Agreement. This review comes at a moment when the AfCFTA implementation and its vehicle, the Guided Trade Initiative (GTI), have been fraught with challenges. Broadly, these challenges include the slow submission of tariff liberalization schedules by State Parties, infrastructure deficits, persistent non-tariff barriers and trade wars in regional economic communities, and overlapping regional trade commitments. Thus, the upcoming AfCFTA review provides an opportunity to assess progress, identify implementation bottlenecks, and propose actionable amendments. This paper examines these challenges through a comprehensive analysis of the AfCFTA's state of play, illuminating the progress while highlighting the slow momentum registered for the past five years of its operation. Proposals for the agreement's amendment revolve on accelerating infrastructure development, harmonizing rules of origin, integrating labor rights, and fostering industrial diversification. By moving beyond liberalization as its raison d'être and prioritizing the scaling up of State Parties' productive capacities, the AfCFTA can evolve from a mere trade liberalization agreement into a transformative driver of Africa's economic renaissance. It is hoped that this timely assessment underscores the urgency of reorienting the AfCFTA to unlock its full potential for propelling intra-Africa trade.
Keywords: 300; Freihandelsabkommen; Wirkungsanalyse; AfCFTA-Staaten